Advanced Signal Processing Techniques Applied to Power Systems Control and Analysis - Bracale, Antonio; Sanjeevikumar, Padmanaban; Leonowicz, Zbigniew; Burgio, Alessandro; Sikorski, Tomasz; Janik, Przemyslaw (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The work published in this book is related to the application of advanced signal processing in smart grids, including power quality, data management, stability and economic management in presence of renewable energy sources, energy storage systems, and electric vehicles. The distinct architecture of smart grids has prompted investigations into the use of advanced algorithms combined with signal processing methods to provide optimal results. The presented applications are focused on data management with cloud computing, power quality assessment, photovoltaic power plant control, and electrical vehicle charge stations, all supported by modern AI-based optimization methods.